Fabrication of Sophisticated Microstructures using Weak Support in 3D Printing. Issue 2 (14th February 2022) - Yu, Zhongwei; Deng, Xinghong; Shao, Guangbin; Li, Longqiu
Abstract : Inside Cover : The cover image presents a lotus and a piece of duckweed floating on water surface, with the outmost cymbiform petals of the lotus half immersed in water. This indicates a new support method in photocuring 3D printing process in which partially cured resin material is used as weak support to fabricate overhang structures or even completely suspended parts, while the weak support is easy to design, fabricate, and remove. Further details can be found in the article 2100613 by Longqiu Li and co‐workers.